Membrane Rafts: Portals for Viral Entry - Ripa, Inés; Andreu, Sabina; López-Guerrero, José Antonio; Bello-Morales, Raquel (Frontiers in Microbiology, 2021)
Membrane rafts are dynamic, small (10-200 nm) domains enriched with cholesterol and sphingolipids that compartmentalize cellular processes. Rafts participate in roles essential to the lifecycle of different viral families including virus entry, assembly and/or budding events. Rafts seem to participate in virus attachment and recruitment to the cell surface, as well as the endocytic and non-endocytic mechanisms some viruses use to enter host cells. In this review, we will introduce the specific role of rafts in viral entry and define cellular factors implied in the choice of one entry pathway over the others. Finally, we will summarize the most relevant information about raft participation in the entry process of enveloped and non-enveloped viruses.